Analysis of the Effect of Smear Zone on Consolidation Decline in the Tebing Tinggi-Kisaran Toll Road Project (Phase 1) Tebing Tinggi – Indrapura STA 102+700 Toll Road Project with 3D PLAXIS Modeling - Annisa Adika Qolby (International Journal of Social Service and Research, 2022)
Repairing of soft clay Embankment loading method with PVD is a soil improvement system consisting of Embankment loading work, installation PVD, installation PHD, and geotechnical instruments. Preload serves to compress the subgrade. PVD serves to speed up the process of soil compaction. Horizontal drains serves to drain pore water taken from the PVD in a horizontal direction to the outside of the location that improved. Geotechnical instruments function to monitor and record the process and determine the performance of the result improving soil that have been carried out. Embankment loading and PVD (Prefabricated Vertical Drain) are technologies that are often used in the construction world to increase shear strength and speed up consolidation time of soft soils. However, during the installation of PVD using a mandrel it can affected the surrounding soil, causing the soil to become disturbed. The disturbed area is called by Smearzone. Due to the presence of a smear area, analysis and calculations are needed to obtain a consolidation time that is in accordance with field conditions. This analysis aims to compare the decrease of displacement in the settlement plate (SP-124) with modeling in PLAXIS 3D considering using with or without taking into account the effect of the smearzone. The method used in this thesis is the analytical method using Terzaghi theory and the finite element method using PLAXIS 3D. From the results obtained analytically the magnitude of the decrease is 15.252 cm while the results from the PLAXIS 3D analysis without the effect of the smear zone is 15.15 cm and with the effect of the smear zone being, 2 times the dimensions of the mandrel the results obtained are 15.131 cm, 15.133 cm and 15.134 cm, with 3 times the dimensions of the mandrel the results obtained are 15,142 cm, 15,141 cm and 15,14 cm and with 4 times the dimensions of the mandrel the results obtained are 15,144 cm, 15,143 cm and 15,143 cm. The decrease that occurs in the settlement plate 124 in the field is 15.10 cm. So it can be concluded that the calculation of consolidation decrease using analytical theory is relatively close to the decrease in actual results in the field with a percentage difference of 1% decrease. There are differences in settlement due to laboratory data not representing the entire soil layer. Due to the decrease that occurred 15.10 cm, the result of the effect of the smear effect 2 times the mandrel dimension and half of the coefficient of permeability of the original soil with a reduction ratio of 0.2% is the result that is closest to the results of field observations compared to without a smear effect of 0.331%.